2014
DOI: 10.1093/toxsci/kfu030
|View full text |Cite
|
Sign up to set email alerts
|

Are Structural Analogues to Bisphenol A Safe Alternatives?

Abstract: Interference with the endocrine system was the predominant effect of the test compounds. A substitution of BPA with these structural analogues should be carried out with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
208
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 371 publications
(233 citation statements)
references
References 68 publications
23
208
0
2
Order By: Relevance
“…BPA and BPE, in the range of concentrations used in the present study, had inhibitory effects on testosterone similar to those in the human testis. In contrast, BPF inhibited testosterone production only weakly in the NCI-H295R cell line, and inhibition by BPS was slight (Rosenmai et al, 2014;Goldinger et al, 2015), consistent with the result in our system after 24 h of exposure. While BPB suppressed testosterone production here (at 10 -7 M at both 24 and 48 h), its anti-androgenicity was close to that of BPA in the NCI-H295R cell line (Rosenmai et al, 2014).…”
Section: Inhibin Bsupporting
confidence: 91%
See 2 more Smart Citations
“…BPA and BPE, in the range of concentrations used in the present study, had inhibitory effects on testosterone similar to those in the human testis. In contrast, BPF inhibited testosterone production only weakly in the NCI-H295R cell line, and inhibition by BPS was slight (Rosenmai et al, 2014;Goldinger et al, 2015), consistent with the result in our system after 24 h of exposure. While BPB suppressed testosterone production here (at 10 -7 M at both 24 and 48 h), its anti-androgenicity was close to that of BPA in the NCI-H295R cell line (Rosenmai et al, 2014).…”
Section: Inhibin Bsupporting
confidence: 91%
“…In contrast, BPF inhibited testosterone production only weakly in the NCI-H295R cell line, and inhibition by BPS was slight (Rosenmai et al, 2014;Goldinger et al, 2015), consistent with the result in our system after 24 h of exposure. While BPB suppressed testosterone production here (at 10 -7 M at both 24 and 48 h), its anti-androgenicity was close to that of BPA in the NCI-H295R cell line (Rosenmai et al, 2014). Further support for our findings comes from a study that used the mouse Leydig cell line, known as the MA-10 cell line (Roelofs et al, 2015).…”
Section: Inhibin Bsupporting
confidence: 91%
See 1 more Smart Citation
“…BPS has been detected in paper currency, paper products, foodstuffs, and urine at concentrations similar to those previously reported for BPA (Liao and Kannan, 2013;Liao et al, 2012a, b). The ability of BPS to activate ER in vitro has been documented (Molina-Molina et al, 2013;Rosenmai et al, 2014), but there is a general lack of in vivo studies for comparison. Kang et al (2014) and Hashimoto et al (2001) indicated that BPS was biotransformed to more potent metabolites after incubation with rat liver S9; whereas, Le Fol et al (2015) performed in vitro biotransformation studies and reported that the conjugates of BPS did not exhibit ER activity.…”
Section: Discussionsupporting
confidence: 76%
“…The limited number of studies available at the present time, dealing with the biological interactions of BPS with the organism, indicate that BPS is also capable of imitating properties of hormones, interacting with ER (Delfosse et al 2012;Rosenmai et al 2014;Le Fol et al 2015), and direct binding to nuclear ERs (Yamasaki et al 2004) and serum albumins (Mathew et al 2014) has been confirmed.…”
Section: Biological Effects Of Bpsmentioning
confidence: 92%